2016
DOI: 10.1108/rsr-01-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Changing the face of reference and user services

Abstract: Purpose Social media allows collaboration, participation and sharing in libraries with users. The purpose of this study is to examine the response of academic librarians in Ghana to the use of social media in reference and user services. Design/methodology/approach It is a quantitative study that used the Likert type of questionnaire in soliciting the views of academic librarians from six public and private universities in Ghana on their knowledge and use of social media in providing reference and user servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The problem, however, is that most private university libraries in Ghana have no professional development policies and hence zero budgetary allocation; this only results in lagging. In the same vein, the authors in [40] found that many library professionals in Ghana are educated and make use of social media platforms for personal and job-related purposes. However, their skills are not enough to use social media tools sequentially to improve library service and hence are resistant to change.…”
Section: Academic Library Industry Challenges and Their Underlying Camentioning
confidence: 94%
“…The problem, however, is that most private university libraries in Ghana have no professional development policies and hence zero budgetary allocation; this only results in lagging. In the same vein, the authors in [40] found that many library professionals in Ghana are educated and make use of social media platforms for personal and job-related purposes. However, their skills are not enough to use social media tools sequentially to improve library service and hence are resistant to change.…”
Section: Academic Library Industry Challenges and Their Underlying Camentioning
confidence: 94%
“…Hamad et al (2017) reported the high social network awareness and substantial utilization for professional development in Jordan libraries. Ahenkorah-Marfo and Akussah (2016) reported that the majority of academic librarians are well-versed in social media and utilize it for both personal and professional purposes. Williams (2018) based on their study of six academic university libraries in Belgium and South Africa reported the increased adoption of social media in these libraries despite financial and infrastructure-related issues.…”
Section: Theoretical Background and Research Frameworkmentioning
confidence: 99%
“…Notwithstanding, from the interview with librarians, it was noted that the library does not have any form of communication service with distance learners and this includes digital reference services. Consequently, it may be concluded that distance education stakeholders and the library has no means of communication, a situation that may lead to distance learners making use of less authoritative information sources (Ahenkorah-Marfo & Akussah, 2016;Ahenkorah-Marfo & Nikoi, 2019). Chawinga and Zozie (2016) found that among three major sources of information for distance learners at a Malawian University, library sources placed last among a list that included lecture notes and internet sources.…”
Section: Distance Learners' Perspectivementioning
confidence: 99%